Depositional constraints of sand-like calcium carbonate particles in the high-calcium cold springs of Huanglong, China: insights from mineralogy, geochemistry, and hydrodynamics - He, Wuyang; Wang, Fudong; Pérez-Mejías, Carlos; Capezzuoli, Enrico; Chen, Shi; Wang, Yanwen; Zhu, Yuyin; Zhao, Xueqin; Dong, Faqin; Zhang, Qingming; Liu, Xinze (Frontiers in Earth Science, 2025)
Calcium carbonate particles are common in many sedimentary environments, with the formational processes unresolved. Due to the variety of sedimentary environments, these particles exhibit significant variations in their petrographic, mineralogical, and geochemical features, as well as their genetic mechanisms. In the Huanglong travertine system, Sichuan, China, unique calcium carbonate particles, resembling sand grains, have been identified and are referred to as sand-like particles (0.5–3.0 mm). This study systematically investigates the mineralogical, petrographic, and geochemical characteristics of these particles. The particles form in a high-Ca2+ cold spring environment (Ca2+ >3.00 mM, T < 13 °C) through an exceptional aggregation-cementation-accretion-compaction process involving both detrital fragments and newformed calcite crystals. The particle growth is primarily controlled by hydrodynamic fluctuations and microbial mediation, with extracellular polymeric substances (EPS) templating calcite nucleation while kinetic disequilibrium drives rapid crystallization. These composite particles preserve distinct microtextural signatures of multiple diagenetic phases, offering new insights into non-classical carbonate formation. This study highlights the complexity and diversity of localized travertine deposition, bridging the gap between macroscopic sedimentary frameworks and localized depositional processes. The Huanglong system represents a unique natural laboratory for studying carbonate sedimentation under hydrochemical gradients. This research provides fundamental insights into the complex interplay between inorganic processes (hydrochemical precipitation driven by high Ca2+ and CO2 degassing) and organic mediation (microbial activity and extracellular polymeric substances) in these unique high-calcium aquatic systems. This not only elucidates the diversity of carbonate deposition mechanisms in Huanglong’s environment, but also holds significant implications for understanding the establishment of similar coupled physicochemical-biological systems in other high-altitude, calcium-rich spring environments worldwide.